Tanggung Jawab Hukum Pelaku Usaha Terhadap Sistem Bundling Dalam Jual Beli - Kania, Victoria; Kuahaty, Sarah Selfina; Pariela, Marselo Valentino Giovani (PATTIMURA Law Study Review, 2025)
Based on Article 15 of Law Number 8 of 1999 concerning Consumer Protection; "Consumer protection is all actions and prohibitions that guarantee legal certainty for business actors, so that consumer rights can be implemented in their business as well as possible." Article 15 Paragraph 2 Number 5 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition; "Business actors are prohibited from making agreements with other parties that contain requirements that the party receiving certain goods and/or services must be willing to purchase other goods and/or services from the supplier business actor." Based on Article 15 of Law Number 8 of 1999 concerning Consumer Protection; "Consumer protection is all actions and prohibitions that guarantee legal certainty for business actors, so that consumer rights can be implemented in their business as well as possible. The method used in this study is the normative juridical legal research method. The problem approach used is a legal approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The procedure for collecting legal materials in this study is a literature study. The management and analysis of legal materials use descriptive methods. The systematics used are in accordance with the guidebook "Guidelines for Writing Thesis, Faculty of Law, Pattimura University. The results of this study indicate that the Bundling practice carried out by business actors in the sale and purchase of their products has committed an unlawful act, which should in carrying out sales and purchase transactions, business actors must refer to the provisions of Article 7, Article 8 and Article 10 of the UUPK. The practice of bundling sales that is contrary to applicable legal regulations, has legal consequences which can be disputed. The legal consequences that arise are that business actors can be sued in court or resolved non-litigation to request compensation for the bundling practices carried out.